2013
DOI: 10.2343/geochemj.2.0262
|View full text |Cite
|
Sign up to set email alerts
|

Isotope and chemical compositions of thermal fluids at Tekman Geothermal Area (Eastern Turkey)

Abstract: The aim of this study was to understand geochemistry of thermal fluids circulating in the basin at the southwest of Tekman (Erzurum, Turkey) Geothermal Province in Eastern Anatolia as well as to estimate reservoir temperature and its heat source by assessment of helium and carbon isotopic compositions of liquid and gas samples.Deep thermal and cold shallow groundwaters are NaCl type (Cerme and Ilipinar springs) and Ca-Mg-HCO 3 type, respectively. The discharge temperatures of thermal waters vary between 29 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…It is emphasized that the geothermal potential of the region in the geochemical studies carried out in Erzurum and its surroundings (Bayraktutan et al 1996;Yuce and Taskiran 2013;Kilic and Inceoz 2015;Kaygusuz et al 2018). Bayraktutan et al (1996) reported signs belonging to the hot spring water in the studies carried out on active faults in Erzurum and its surroundings.…”
Section: The Origin Of Geothermal Fluidsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is emphasized that the geothermal potential of the region in the geochemical studies carried out in Erzurum and its surroundings (Bayraktutan et al 1996;Yuce and Taskiran 2013;Kilic and Inceoz 2015;Kaygusuz et al 2018). Bayraktutan et al (1996) reported signs belonging to the hot spring water in the studies carried out on active faults in Erzurum and its surroundings.…”
Section: The Origin Of Geothermal Fluidsmentioning
confidence: 98%
“…Bayraktutan et al (1996) reported signs belonging to the hot spring water in the studies carried out on active faults in Erzurum and its surroundings. Yuce and Taskiran (2013) found that the thermal waters had deep mantle traces and these waters were magmaic based, as a result of the analysis of gas and water samples taken from thermal waters with the temperature of 57 degrees. Kaygusuz et al (2018) reported that magmatic materials were transported along active tectonic units in the study carried out by Kandilli and its vicinity.…”
Section: The Origin Of Geothermal Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low Mg content of thermal waters can be explained by the absorption of Mg in high-temperature geothermal systems. As the geothermal fluids flow from a high temperature to a low temperature environment, it appears to adsorb large amounts of Mg into contacting host rocks [13,18]. The occurrence of Mn in thermal water might be due to the dissolution of secondary Mn-bearing minerals that are associated with epithermal activity.…”
Section: Geochemical Compositionsmentioning
confidence: 99%
“…Chemical compositions of the groundwaters (MG) are of the Ca-HCO 3 type, whereas the thermal waters (MH) can be chemically divided into a Na-HCO 3 type at lower temperatures (type I) and an Na-Cl (HCO 3 − , SO 4 2− ) type at higher temperatures (type II). It is generally considered that, in the geochemical evolution of thermal waters and deep groundwater in granite and gneiss areas of South Korea, the waters are of the Ca-HCO 3 type initially, progressing through the Ca(Na)-HCO 3 type to the alkaline Na-HCO 3 type in the final stage [13,19]. The two different types of thermal water appear to have evolved in different geological environments.…”
Section: Geochemical Compositionsmentioning
confidence: 99%